Impact of neutron radiation on the viability of tumor cells cultured in the presence of boron-10 isotope - O. Yu. Volkova; L. V. Mechetina; A. V. Taranin; A. A. Zaboronok; K. Nakai; S. I. Lezhnin; S. A. Frolov; D. A. Kasatov; A. N. Makarov; I. N. Sorokin; T. V. Sycheva; I. M. Shchudlo; et al. (Вестник рентгенологии и радиологии)
Objective: to investigate the impact of a neutron beam formed with the accelerator-based epithermal neutron source designed at the G.I. Budker Institute of Nuclear Physics (INP) on the viability of human and animal tumor cells cultured in the presence of boron-10 isotope.Material and methods. Human U251 and T98G glioma cells and Chinese hamster CHO-K1 and V-79 cells were incubated at various concentrations in the culture medium containing 10B-enriched L-boronophenylalanine. The cells were irradiated with a neuron beam using the accelerator-based epithermal neuron source. A clonogenic assay was used to evaluate the viability of the irradiated cells. The absorbed doses obtained from elastic scattering of fast neutrons by substance nuclei and the doses obtained from boron neutron capture were calculated using the NMS code. The absorbed doses of gamma-radiation were measured with a mixed radiation dosimeter.Results. The viability of boron-containing and intact human U251 and T98G cell lines and Chinese hamster CHO-K1 and V-79 cells was analyzed after neutron beam radiation. Irradiation of all four cell lines were cultured in the presence of 10B was shown to reduce their colony-forming capacity compared with the control. Elevated boron levels in the culture medium resulted in a significant decrease in the proportion of survived cells. Radiation had the most pronounced impact on the proliferative capacity of the human U251 glioma cell lines.Conclusion. The cultures of human tumor cells and mammalian cells demonstrated that the neutron beam formed with the accelerator-based epithermal neutron source designed at the INP, was effective in reducing the viability of tumor cells in the presence of 10B